Oncolytic Adenovirus-Based Immunotherapy for Malignant Mesothelioma: Preclinical Advances and Future Perspectives - Garofalo Mariangela; Staniszewska Monika; Salmaso Stefano; Caliceti Paolo; Kuryk Lukasz (Postępy Mikrobiologii, 2025)
Malignant mesothelioma is a rare but highly aggressive cancer, with an incidence of approximately 1–2 cases per million per year in industrialized countries and a global annual mortality exceeding 30,000 cases. The disease is caused mainly by exposure to asbestos and is resistant to conventional treatment modalities, resulting in poor outcomes. Standard approaches include surgery, chemotherapy, and, more recently, immune checkpoint inhibitors. However, owing to the aggressive nature of cancer, the prognosis is poor, with limited treatment options. Globally, the disease accounts for more than 30,000 deaths annually. Current treatment efficacy remains suboptimal, particularly in advanced stages. Oncolytic virotherapy, especially adenovirus-based vectors, has emerged as a novel immunotherapeutic strategy with the potential to induce tumour lysis and stimulate antitumour immunity. This review summarizes the current treatment landscape for mesothelioma and highlights preclinical and early clinical findings on engineered oncolytic adenoviruses, particularly those expressing ICOSL, CD40L, and OX40L, and their promising synergistic effects with checkpoint blockade and chemotherapy. Furthermore, in this review, we present insights from clinical studies of the effects of adenovirus Ad5/3-D24-GM-CSF on mesothelioma and discuss promising avenues for future immunotherapy.